1991
DOI: 10.1182/blood.v77.10.2109.2109
|View full text |Cite
|
Sign up to set email alerts
|

Combined therapy with recombinant granulocyte colony-stimulating factor and erythropoietin decreases hematologic toxicity from zidovudine

Abstract: Twenty-two patients with acquired immunodeficiency syndrome (AIDS) or severe AIDS-related complex and multilineage hematopoietic defects were treated with recombinant granulocyte colony-stimulating factor (G-CSF) and erythropoietin (EPO) in a phase I/II trial. All patients were neutropenic and anemic after withdrawal of all bone marrow-suppressive drugs. Daily, G-CSF was subcutaneously self-administered until an absolute neutrophil count (ANC) greater than 6,000/microL was achieved and maintained for 2 weeks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The same investigators also identified two patients with defective bacterial killing mechanisms (one in phagocytosis and one in intracellular killing), but these, too, appeared to be corrected by GM-CSF (14). Subsequent studies have shown both G-CSF and GM-CSF to be very effective in correcting the neutropenias seen with zidovudine therapy alone (311) or combined with interferon, and the two CSFs have allowed treatment to continue in patients otherwise unable to tolerate it because of bone marrow toxicity (92,408). This has been true of patients with advanced (408) as well as early (92) HIV disease.…”
Section: Immunomodulatorsmentioning
confidence: 97%
“…The same investigators also identified two patients with defective bacterial killing mechanisms (one in phagocytosis and one in intracellular killing), but these, too, appeared to be corrected by GM-CSF (14). Subsequent studies have shown both G-CSF and GM-CSF to be very effective in correcting the neutropenias seen with zidovudine therapy alone (311) or combined with interferon, and the two CSFs have allowed treatment to continue in patients otherwise unable to tolerate it because of bone marrow toxicity (92,408). This has been true of patients with advanced (408) as well as early (92) HIV disease.…”
Section: Immunomodulatorsmentioning
confidence: 97%
“…Patients with AIDS may undergo primary bone marrow failure or myelosuppression due to antiviral or supportive anti-infection therapy. G-CSF has demonstrated marked improvements in neutrophil counts in patients with anemia and neutropenia also receiving erythropoietin and zidovudine [41]. Such therapy allowed further treatment with zidovudine after zidovudine-induced myelosuppression was corrected.…”
Section: Colony-stimulating Factorsmentioning
confidence: 98%
“…After the intravenous or intraorgan infection with HIV-1, only human cells were infected and from these, only CD4+ T and myelomonocytic cells. Initial HIV-1 infections of SCID-hu Thy/Liv animals resulted in a near-eradication of CD4+/CD8+ DP thymocytes and a decrease in the CD4+ SP T cell population of the human implanted tissue [ 77 , 87 , 88 ], a depletion shown to be reduced upon treatment with several anti-HIV compounds [ 89 - 93 ] (Table 3 ).…”
Section: Humanized Murine Models Of Hiv-1 Infectionmentioning
confidence: 99%